miR-10b-3p, miR-8112 and let-7j as potential biomarkers for autoimmune inner ear diseases - Zhang, Juhong (Mol Med Rep, 2019)
Circulating microRNAs (miRNAs) have been suggested as non-invasive biomarkers for the diagnosis of several autoimmune diseases. However, to the best of our knowledge, no studies have yet examined the miRNA expression profiles in autoimmune inner ear disease (AIED). The present study aimed to use an miRNA sequencing assay to detect the miRNA expression profiles of serum samples from 3 control mice and 3 antigen-induced AIED model mice. Differentially expressed miRNAs (DE-miRNAs) were screened using a t-test. miRNA target prediction was performed using TargetScan Mouse. Then, the miRNA-target gene interaction network was constructed and visualized using Cytoscape software. The underlying functions of the target genes of the DE-miRNAs were predicted using the clusterProfiler package. As a result, 22 miRNAs were identified as DE-miRNAs between AIED and control mice, including 10 upregulated and 12 downregulated genes. Based on the TargetScan Mouse prediction, 1,958 genes were identified as the targets for the 22 DE-miRNAs. Functional analysis indicated that only the target genes of 8 miRNAs were respectively enriched for Gene Ontology terms and Kyoto Encyclopedia of Genes and Genomes pathways, among which miR-10b-3p, let-7j and miR-8112 were shared between the two pathway analyses. These 3 miRNAs may be involved in AIED by affecting inflammatory chemokine (miR-10b-3p-C-C motif chemokine 12), Wnt signaling (miR-8112-Wnt9b/Wnt 3a/Wnt2b) and Mucin type O-glycan biosynthesis pathways (let-7j-Galnt2/Galnt12). In conclusion, miR-10b-3p, miR-8112 and let-7j may be underlying biomarkers for diagnosing AIED.